2009
DOI: 10.1111/j.1399-3054.2009.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and co‐regulation of carrot AOX genes (Daucus carota)

Abstract: Alternative oxidase (AOX) is a mitochondrial protein encoded by the nuclear genome. In higher plants AOX genes form a small multigene family mostly consisting of the two subfamilies AOX1 and AOX2. Daucus carota L. is characterized by a unique extension pattern of AOX genes. Different from other plant species studied so far it contains two genes in both subfamilies. Therefore, carrot was recently highlighted as an important model in AOX stress research to understand the evolutionary importance of both AOX subfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…In the present study, the DcAOX2a and DcAOX1a genes were chosen for correlation studies with phenylpropanoid biosynthesis because of known involvement of these two AOX genes in the process of developmental and cell reprogramming Frederico et al, 2009). Recently, Campos et al (2009) showed developmental and tissue specific differential transcript accumulation of DcAOX2a and DcAOX1a in D. carota. A parallel result was obtained in Arabidopsis thaliana, where AtAOX2 was differentially expressed during developmental stages (Clifton et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the DcAOX2a and DcAOX1a genes were chosen for correlation studies with phenylpropanoid biosynthesis because of known involvement of these two AOX genes in the process of developmental and cell reprogramming Frederico et al, 2009). Recently, Campos et al (2009) showed developmental and tissue specific differential transcript accumulation of DcAOX2a and DcAOX1a in D. carota. A parallel result was obtained in Arabidopsis thaliana, where AtAOX2 was differentially expressed during developmental stages (Clifton et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Multiple sequence alignment was performed using the ClustalW platform in the BioEdit software (Campos et al, 2009). The alignment result was fit into MEGA 5.05 (Tamura et al, 2011) to construct a phylogenetic tree by the neighbor-joining method.…”
Section: Construction Of a Phylogenetic Treementioning
confidence: 99%
“…Recently, AOX genes have been isolated from D. carota (Campos et al 2009, Cardoso et al 2009, Costa et al 2009). The D. carota AOX ( DcAOX ) multigene family consists of two genes from the subfamily AOX1 and two genes from the subfamily AOX2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, both genes of each subfamily demonstrated differential activities among each other. Typically, higher transcript accumulation and responsiveness were found for the two genes DcAOX1a and DcAOX2a and co‐regulation of both was demonstrated during de novo growth induction (Campos et al 2009).…”
Section: Introductionmentioning
confidence: 99%